2018
DOI: 10.1007/s00784-018-2409-y
|View full text |Cite
|
Sign up to set email alerts
|

Micro-computed tomography-based anatomical study of the branch canals in mandibular anterior teeth in a Chinese population

Abstract: This knowledge may be employed as a guide in clinical endodontic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Micro-computed tomography is able to provide accurate and quantifiable results, thus, is considered as the gold standard when investigating RCCs 18 . However, relative few studies have investigated the MaCa root canal morphology by means of micro-computed tomographic imaging 12 14 , 29 . The RCC description systems proposed by Vertucci 19 and Weine et al 3 have been widely reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-computed tomography is able to provide accurate and quantifiable results, thus, is considered as the gold standard when investigating RCCs 18 . However, relative few studies have investigated the MaCa root canal morphology by means of micro-computed tomographic imaging 12 14 , 29 . The RCC description systems proposed by Vertucci 19 and Weine et al 3 have been widely reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although CBCT images do not provide images that are as high-resolution as those of micro-CT, it appears to be a good method to examine root canal configurations [ 3 , 43 ]. Few studies have investigated the MaCa root canal morphology by means of micro-CT [ 33 , 34 , 37 , 38 ]. However, those investigating morphological parameters different from the ones in the systematic review investigated other topics than root canal configuration; thus, they did not meet the inclusion criteria and could not be considered in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Cone-beam computed tomography (CBCT) and micro-computed tomography (micro-CT) are the two most recently introduced investigation methods, and CBCT has been predominantly used for in vivo investigation of the morphology of the root canal system of mandibular canines (MaCa) [ 6 , 13 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Although micro-CT has already been used to examine various teeth as well as to describe the internal morphology of mandibular canines, it has not yet been used to identify the root canal configuration [ 3 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, several methodologies have been used for the study of the internal root anatomy of mandibular incisors (MI), including canal staining and tooth clearing (2)(3)(4)(5), radiographs (6)(7)(8)(9)(10), cone-beam computed tomography (11)(12)(13)(14)(15)(16)(17)(18)(19) and high-resolution computed tomography (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%